Characteristic physical traits of first‐grade children in the United States with fetal alcohol spectrum disorders (FASD) and associated alcohol and drug exposures. Issue 7 (31st March 2022) - May, Philip A.; Hasken, Julie M.; Manning, Melanie A.; Robinson, Luther K.; Abdul‐Rahman, Omar; Adam, Margaret P.; Jewett, Tamison; Elliott, Amy J.; Kalberg, Wendy O.; Buckley, David; Hoyme, H. Eugene
Abstract: We compared growth, physical features, and minor anomalies in 131 first‐grade children with fetal alcohol spectrum disorders (FASD) to those of a representative comparison group of typically developing children from the same populations ( n = 1212). The data were collected from three regional sites in the NIAAA‐funded Collaboration on FASD Prevalence (CoFASP). Dysmorphology examinations were performed by a team of expert clinical geneticists, and FASD diagnoses were assigned according to the Revised Institute of Medicine Guidelines, which include assessments of growth, dysmorphology, neurobehavior, and maternal risk interviews. We present detailed data on 32 physical traits, minor anomalies, and a summary dysmorphology score for children within each of the four diagnostic categories in the continuum of FASD. There were few differences in the frequency of FASD diagnoses by race or Hispanic ethnicity. Children with FASD were born to mothers who reported using alcohol, tobacco (28.3%), and other drugs (14.2%) during pregnancy. Controlling for tobacco and other drug use, risk analysis indicated that women with a drinking pattern of 3 drinks per drinking day prior to pregnancy were 10 times more likely ( p < 0.001, OR = 9.92, 95% CI: 4.6–21.5) to bear a child with FASD than those who reported abstinence prior to pregnancy.